Perancangan Sistem Informasi Penjualan Ritel Berbasis Web Menggunakan Metodologi Waterfall - Dzakwan Abbas; Muhammad Irwan Padli Nasution (CV. Multi Kreasi Media, 2026)
This study discusses the development of a web-based sales information system to support the operations of Micro, Small, and Medium Enterprises (MSMEs) by applying the Waterfall methodology. The developed system includes main features such as product management, transaction processing, sales reporting, and user authentication. Manual testing using 10 test scenarios showed a functional success rate of 80%. The system implementation was able to speed up transaction time from five minutes to approximately forty-five seconds and reduce manual input errors by up to 75%. Usability evaluation using the System Usability Scale (SUS) resulted in a score of 84, indicating a very high level of user acceptance. The results of this study show that a web-based sales information system developed using the Waterfall approach can improve efficiency, accuracy, and effectiveness in managing sales for MSMEs.